Enhancing Vocabulary Mastery through the Use of Authentic Material - Nabila Imtiyaaz Hanifah; K. Dedy Sandiarsa S; Baiq Sumarni; Heri Hdayatullah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aimed to improve students’ vocabulary mastery through the use of authentic materials in the form of poster advertisements. The research was conducted at class VII B of SMPN 1 Mataram in the academic year 2025/2026. This study employed Classroom Action Research (CAR) consisting of two cycles, each including planning, acting, observing, and reflecting stages. The subjects of the study were 44 students of class VII B. The instruments used in this research were vocabulary tests and observation checklists. Quantitative data were obtained from students’ pre-test and post-test scores, while qualitative data were collected through classroom observations focusing on teacher activities during the teaching and learning process. The findings showed a significant improvement in students’ vocabulary mastery. In Cycle 1, the mean score increased from the pre-test to the post-test, reaching a mean score of 69.64, with only 17 students (38.6%) achieving scores above the Minimum Mastery Criterion (KKM) of 75. After revising the teaching material by integrating poster advertisements in Cycle 2, the mean score increased to 89.45, and 42 students (95.4%) achieved scores above the KKM. Based on the findings, it can be concluded that the use of authentic materials, particularly poster advertisements, effectively improved students’ vocabulary mastery. Therefore, authentic materials are recommended as an alternative teaching material to enhance vocabulary learning in junior high school students.